Wh-Movement in Iraqi Dialect - Khudhur, Sohaib Mahmood (International Journal of Linguistics, 2023)
Changes in the word's position and the structure's construction are a system by which some words move from one position to another due to linguistic factors such as morphology and syntax. This movement is not limited to words alone; it is also possible in phrases. Constraints that regulate the movement process also govern these changes. The syntactic structure is a commonly influenced linguistic aspect in dialect languages. The sentence structure, including all types of sentences, varies according to dialect. The study of interrogatives, whether in Iraqi dialects or not, is significant. One of the two dominant dialects, Mosuli or Baghdadi, can serve as an excellent representative for the remaining subdialects. This paper will contribute to our understanding of the structure of interrogatives in the Iraqi dialect and the movement that occurs in various sentence positions.